2022
DOI: 10.1093/nsr/nwac040
|View full text |Cite
|
Sign up to set email alerts
|

Redox mediators for high-performance lithium–oxygen batteries

Abstract: The aprotic lithium-oxygen (Li-O2) batteries are receiving intense research interest in virtue of their ultra-high theoretical specific energy. However, current Li-O2 batteries are sufferring from severe barriers, such as sluggish reaction kinetics and undesired parasitic reactions. Recently, molecular catlysts, i.e., redox mediators (RMs), have been explored to catalyze the oxygen electrochemistry in Li-O2 batteries and are regarded as an advanced solution. To fully unlock the capability of Li-O2 batteries, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 84 publications
(40 citation statements)
references
References 94 publications
0
40
0
Order By: Relevance
“…In the past decade, a number of excellent books and review articles have been published regarding non-aqueous or aqueous Li–air batteries ( Feng et al, 2016 ; Kwak et al, 2020 ; Dou et al, 2022 ; Liu et al, 2022 ), but the latest article for the aqueous Li–air battery has been published for more than 3 years, best to our knowledge ( Imanishi and Yamamoto, 2019 ). As significant approaches have been made day by day, it is necessary to summarize and review them in order to accelerate the research pace for the application of aqueous Li–air batteries.…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, a number of excellent books and review articles have been published regarding non-aqueous or aqueous Li–air batteries ( Feng et al, 2016 ; Kwak et al, 2020 ; Dou et al, 2022 ; Liu et al, 2022 ), but the latest article for the aqueous Li–air battery has been published for more than 3 years, best to our knowledge ( Imanishi and Yamamoto, 2019 ). As significant approaches have been made day by day, it is necessary to summarize and review them in order to accelerate the research pace for the application of aqueous Li–air batteries.…”
Section: Introductionmentioning
confidence: 99%
“…Redox mediators (RMs), soluble catalysts in an electrolyte, have been confirmed to be high-efficiency diffusive catalysts for the cathode reactions. , They act as electron–hole “carriers” between the electrode surface and Li x O y , facilitating the decomposition of Li x O y , irrespective of the size and the structure of Li x O y . Since Bruce et al reported tetrathiafulvalene (TTF) as an effective RM for LOBs in 2013, various kinds of RMs (organic, organometallic, and halide) have been developed. Among them, organometallic RMs are particularly attractive because their redox properties can be flexibly tuned by replacing the center active transition metal ions and/or modifying the organic ligands. , In addition, recent studies have revealed that RMs can induce an increased intersystem crossing rate and suppress 1 O 2 formation during the ORR and OER processes, thereby reducing parasitic reactions. , Notably, the organic RMs themselves can also be predominantly decomposed and deactivated by 1 O 2 , leading to limited efficiencies of 1 O 2 suppression. , Thus, it is essential to find a way to operate LOBs via a chemical step that does not form 1 O 2 .…”
mentioning
confidence: 99%
“…12,13 They act as electron−hole "carriers" between the electrode surface and Li x O y , facilitating the decomposition of Li x O y , irrespective of the size and the structure of Li x O y . 14 Since Bruce et al reported tetrathiafulvalene (TTF) as an effective RM for LOBs in 2013, 13 various kinds of RMs (organic, organometallic, and halide) have been developed. 15−18 Among them, organometallic RMs are particularly attractive because their redox properties can be flexibly tuned by replacing the center active transition metal ions and/or modifying the organic ligands.…”
mentioning
confidence: 99%
“…Toward unlocking the potential of Li–O 2 batteries, considerable efforts were devoted to governing the formation of Li 2 O 2 in electrolytes (i.e., Li 2 O 2 (sol)), termed as the solution-route ORR . Although strong-solvation electrolytes or functional additives can achieve this goal by regulating the solubility and/or reactivity of superoxide species, such systems are vulnerable due to the decreased electrolyte stability and increased parasitic reactions with Li anodes. Recently, soluble redox mediators (RMs) have demonstrated their ability to modulate the formation pathway and deposition behavior of Li 2 O 2 . Upon operation, the electrochemically reduced RMs chemically reduce O 2 to Li 2 O 2 while recovering to the pristine neutral state. Mediators allow, in principle, the reduction of O 2 in electrolytes away from the electrode surface, resulting in significant remission of cathode passivation. , …”
mentioning
confidence: 99%